The Acquisition and Utilization of Power Resources: Kenyan Trade Union Revitalization - Jacob Omolo (Modern Perspectives in Economics, Business and Management Vol. 1, 2021)
In trade union studies, it has become clear that trade unions are not exclusively at the mercy of big societal trends, but that they always have the option of adopting strategic decisions to revive and improve their members' socioeconomic well-being. The key question is, which power resources and means of exerting such power are available to trade unions in the different context they face to reposition and revitalize themselves? The power resources technique is used in this study to determine the power resources that the Kenya National Private Security Workers Union acquired, developed, and used to revitalise. The revitalization process began in 2011, and since then, the union has gone from being characterised by leadership squabbles, coups, demarcation conflicts, and low membership density to one with a relatively high membership, stronger cohesion and solidarity, and unity among the leadership and rank and file members. The revitalization of the Kenya National Private Security Workers Union, according to the analysis, reinforced the conclusion that associational power is best sustained through institutional power. The revitalization process also served a dual purpose, allowing the union to gain public sympathy and relevance while also providing it the internal articulation capabilities to bring together national officials, shop stewards, and rank-and-file members. Between 2011 and 2017, the union's density increased nearly tenfold as a result of these changes. It also helped the union grow into a powerful, unified, and energetic organisation capable of turning challenges into opportunities.